Prevalence and Associated Risk Factors of Postpartum Hemorrhage in Tertiary Care Hospitals of Pakistan. A Cross-Sectional Study - Sakina Naeem, Nusrat Fozia Pathan, Bushra Noor Khuhro, Afshan Mushtaq, Arifa Inayat, Saima Iram (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum hemorrhage (PPH) still ranks as a major cause of maternal morbidity and mortality, especially in low and middle-income countries. The objective of this study was to find the prevalence of PPH and its risk factors among postpartum women in tertiary care hospitals of Pakistan. Methods: It is a cross-sectional study done at Sandeman Provincial Hospital, Quetta, and KMC Civil Hospital, Khairpur, from January 2022 to December 2022. Systematic random sampling was used to include a total of 120 postpartum women with complete medical records. Retrospectively, data on demographic characteristics, obstetric history, clinical parameters, and biomarkers (haemoglobin levels, coagulation profiles, and C reactive protein) were obtained. SPSS version 25 statistical analyses were conducted with chi-square tests and multivariate logistic regression to determine independent predictors of PPH. Statistically significant was set at a p-value <0.05. Results: The prevalence of PPH was 8.3%. In the absence of fetal demise, advanced maternal age (≥35 years), multiparity, prolonged labor (≥18 hours), anemia (hemoglobin <11 g/dL), and elevated C-reactive protein levels (>10 mg/L) were all significant independent risk factors for PPH. The odds of PPH were 2.5 times higher (OR = 2.5; 95% CI: 1.4–4.5; p = 0.002) with prolonged labor. Conclusion: The findings suggest that PPH is a multifactorial disease, with both demographic and clinical factors acting to increase its occurrence. These results emphasize the importance of comprehensive antenatal screening and careful peripartum care to reduce PPH risks. Early detection and management of anemia, as well as monitoring labor duration and inflammatory status, are suggested as targeted interventions to improve maternal outcomes. Keywords: Postpartum hemorrhage, maternal morbidity, tertiary care hospitals, Pakistan, risk factors, anemia, prolonged labor, C-reactive protein.